Identification of Microplastics in The Outer Ambon Bay, Mollucas - Lekatompessy, Vanela Chatrin; Marhendra, Agung Pramana Warih; Kurniawan, Nia (The Journal of Experimental Life Science, 2024)
Marine plastic debris that enters the sea can be fragmented by physical and chemical factors, then float in the water column or accumulate in sediments, which have the potential to be ingested by marine biota, causing digestive system disorders, fecundity, eating capacity, reproduction, and death. This study aimed to identify the accumulation of microplastics in water and sediments in Outer Ambon Bay using a purposive sampling method and descriptive analysis for data related to microplastics' type, color, and size, as well as follow-up tests of the least significant difference. The results show that the waters of Outer Ambon Bay have been polluted by microplastics. The number of microplastic particles found in water samples at three different depths (0, 50, and 100 cm) was 201 particles L-1, and in sediment samples, it was 325 particles g-1. It is supported by the fact that the type of fiber has a thin shape and size and can float on the surface of the water and by the existence of beaches where there are fishing activities, boat ports, rivers, and densely populated areas, as well as sandy and muddy sediments that can trap more microplastics during the tidal period. Therefore, it is necessary to prevent the waste problem in the waters of Ambon Bay. Keywords: Identification, Marine Pollution, Microplastics, Outer Ambon Bay.